PMO-148 Evaluation of liver fibrosis in young adult patients with chronic hepatitis B virus. (28th May 2012) - Patel, C; Gill, U S; Alazawi, W; Shaw, P; Alstead, E; Kallis, Y; Kooner, P; Marley, R; Naik, S; ChinAleong, J; Goldin, R D; Foster, G R; et al.
Abstract : Introduction: Current guidelines do not recommend treatment of Chronic Hepatitis B (CHB) in young adults as they are believed to be immune tolerant with minimal liver damage. Recently we demonstrated that young CHB patients have evidence of immune activity comparable to older patients. Therefore, a proportion of young patients will develop fibrosis as a consequence of immune mediated liver injury. Despite this, the most appropriate modality to assess liver fibrosis remains controversial. We compare the utility of liver biopsy and digital image analysis with FibroScan for assessment of CHB in young adults. Methods: Young adult CHB patients were followed in a dedicated clinic and seen 3-monthly. Liver biopsy was performed where indicated and compared with FibroScan scores. Digital image analysis was performed on a selected number of Sirius red stained sections to evaluate percentage fibrosis. 167 patients were assessed; 101/167 (male=63); median age 26 (range 16–30) underwent liver biopsy and were included for analysis. Results: 47/101 patients were eAg+. Overall median ALT was 41IU/L (range 14–426) & HBV DNA was 5.22 logIU/ml (range 1.4–9.3). Median Ishak fibrosis score was 1 (range 0–6); median FibroScan score was 5.95 kPa (range 2.6–35.2). There was no difference in the FibroScan score in patients with advanced (F5/6) and minimal fibrosis (F0/1); median FibroScan scores were 6 and 5.95 respectively, (p=ns). The correlation co-efficient between fibrosis and FibroScan was not statistically significant (p=0.46). FibroScan scores were confounded by ALT; using Prati criteria to define normal ALT (female <19 IU/l, male <30 IU/l), we noted an ALT twice ULN revealed a higher FibroScan score, regardless of fibrosis (p=0.05 and 0.04; males and females respectively). On the contrary, digital image analysis more accurately reflected fibrosis stage irrespective of ALT. Conclusion: A proportion of young adult patients with CHB have significant liver disease on biopsy. This study highlights the limitations of FibroScan in assessing liver fibrosis in this cohort. Our data demonstrates the utility of digital image analysis in benchmarking fibrosis in young patients, potentially providing a more accurate methodology to assess progression of fibrosis over time. Competing interests: None declared.